The Importance of The Exchange Rate in Public Procurement on The Example of The Polish Market in The Context of Unfinished Monetary Integration with The Euro Area - Jaroslaw Czaja (Communications of International Proceedings, 2023)
The importance of the zloty exchange rate against the euro in public procurement in the context of monetary integration with the European Union. The content of this article refers to determining the meaning of the euro exchange rate and expressing the value of goods and services in it in the Polish procurement law in the period 2004-2023. The article also takes into account the specificity of shaping the levels of this EURPLN rate. The importance of a selective derogation in favor of the Polish zloty in the Public Procurement Law under the so-called sub-threshold orders, which is a noticeable change in the until recently strong attitude (these processes have slowed down) to the use of the euro as part of the broadly understood monetary integration of the new EU member states. Member States retain the possibility of derogating from the Public Procurement Law for transactions below the EU thresholds in order to protect their internal markets against the effects of incomplete monetary integration. The literature lacks extensive research on the interaction between the exchange rate and the Public Procurement Law, and the presented publication is an attempt to fill this gap. For the analysis, time series of the Polish zloty exchange rate against the euro, provided by the National Bank of Poland and in the executive acts of the Prime Minister and in the announcements of the President of the Public Procurement Office, referring to the relevant acts of EU law.
Keywords: public procurement law; monetary integration; exchange rate; European Union; euro currency